2002
DOI: 10.1103/physrevlett.88.137401
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Decay Time of Single Semiconductor Nanocrystals

Abstract: We present fluorescence decay measurements of single ZnS covered CdSe nanocrystals. It is shown that the fluorescence decay time is fluctuating during the investigation leading to a multiexponential decay even for a single nanocrystal. In combination with measurements of the fluorescence blinking behavior we find that a high fluorescence intensity is correlated with a long fluorescence decay time. This is consistent with a model of fluctuating nonradiative decay channels leading to variable dynamic quenching p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
454
2
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(498 citation statements)
references
References 21 publications
40
454
2
2
Order By: Relevance
“…Other multiexponential models are the heuristic biexponential model and the Kohlrausch stretched exponential model that has been employed to QDs outside photonic crystals. 22,24 Figure 2 shows that the biexponential model does not match our data, even though more free parameters are involved. The stretched exponential model does not match our data either, 23 which again confirms that the variations we observe are due to LDOS effects in photonic crystals and not to complex emission properties of the QDs.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Other multiexponential models are the heuristic biexponential model and the Kohlrausch stretched exponential model that has been employed to QDs outside photonic crystals. 22,24 Figure 2 shows that the biexponential model does not match our data, even though more free parameters are involved. The stretched exponential model does not match our data either, 23 which again confirms that the variations we observe are due to LDOS effects in photonic crystals and not to complex emission properties of the QDs.…”
Section: Resultsmentioning
confidence: 89%
“…͑iv͒ It was suggested in Ref. 22 that temporal fluctuations of the environment surrounding the QDs induce a distribution of nonradiative decay channels. In our experiments,…”
Section: Resultsmentioning
confidence: 99%
“…40 In the case of simple biexponential analysis it is assumed that each dot's emission lifetime is made up of two components 41,42 and the shorter lifetime,  1 , is typically attributed to the intrinsic recombination of the initially populated core states. [43][44][45][46] The origin of the longer component  2 , although long disputed, is now considered to be a result of the interference of surface states (i.e. the presence or absence of surface defects), with the recombination of the electron-hole pairs.…”
Section: Discussionmentioning
confidence: 99%
“…The trend that could be extrapolated, based on the few available experimental data [19][20][21][22][23] for NQDs of different sizes, was that of a slight decrease of the radiative lifetime with increasing dot size. However, a recent experimental paper by van Driel et al [18] showed an increase of the radiative lifetime with size for CdSe quantum dots at room temperature (see Fig.…”
Section: Size-dependence Of the Exciton Radiative Lifetime And Commentioning
confidence: 99%